(untitled) (Politeja, 2023)
CLOUD GATE DANCE THEATRE IN SEARCH OF CHINESE AND TAIWANESE CULTURAL IDENTITY This paper shows the dynamics of topical, aesthetical and political changes in the world-known contemporary dance group – Cloud Gate Dance Theatre of Taiwan (Yunmen Wuji), created by Lin Hwai-min in 1973. Those metamorphoses are observed in a broad socio political and cultural context, in the rapidly changing reality of Taiwan, Mainland China and the whole world at the turn of the 20th and 21st century. Short analyses of the most iconic dance compositions by Lin Hwai-min make it possible to trace the direction of the changes, starting from search for Chinese cultural identity, through the quest for definition of Taiwanese cultural and national identity, gaining the feeling of being rooted in traditional Chinese aesthetics and finally confirming the importance of local Taiwanese tradition as an equally meaningful source of creative inspiration.